Women Entrepreneurs: we cannot have change unless we have men in the room - Irene Kamberidou (Journal of Innovation and Entrepreneurship, 2013)
<dl id="citeas" class="citation-info u-highlight-target u-mb-16"> Cite this article as: Kamberidou, I. J Innov Entrep (2013) 2: 6. https://doi.org/10.1186/2192-5372-2-6 </dl> DOI https://doi.org/10.1186/2192-5372-2-6 Publisher Name Springer Berlin Heidelberg Online ISSN 2192-5372 About this journal <a id="reprintsandpermissions-link" class="u-external" href="https://s100.copyright.com/AppDispatchServlet?publisherName=Springer&orderBeanReset=true&orderSource=SpringerLink&author=Irene+Kamberidou&authorEmail=irene.kamberidou%40womenandtechnology.eu&issueNum=1&contentID=10.1186%2F2192-5372-2-6&openAccess=true&publicationDate=2013&startPage=6&volumeNum=2&title=Women+entrepreneurs%3A+%E2%80%98we+cannot+have+change+unless+we+have+men+in+the+room%E2%80%99&imprint=Kamberidou%3B+licensee+Springer.&publication=2192-5372&authorAddress=Gr%C3%B8nland+58%2C+Drammen%2C+N-3045%2C+Norway" target="_blank" title="Visit RightsLink for information about reusing this article">Reprints and Permissions